2013
DOI: 10.2337/db12-1042
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids Reduce Adipose Tissue Macrophages in Human Subjects With Insulin Resistance

Abstract: Fish oils (FOs) have anti-inflammatory effects and lower serum triglycerides. This study examined adipose and muscle inflammatory markers after treatment of humans with FOs and measured the effects of ω-3 fatty acids on adipocytes and macrophages in vitro. Insulin-resistant, nondiabetic subjects were treated with Omega-3-Acid Ethyl Esters (4 g/day) or placebo for 12 weeks. Plasma macrophage chemoattractant protein 1 (MCP-1) levels were reduced by FO, but the levels of other cytokines were unchanged. The adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
134
2
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(151 citation statements)
references
References 46 publications
7
134
2
3
Order By: Relevance
“…Our results document that 13-DHAHLA has the ability to affect immune cells, alleviate macrophage activation, and stimulate the proresolving processes. It is conceivable that DHAHLA may contribute to the anti-inflammatory and proresolving effects attributed to the DHA in human and murine WAT (lower density of crown-like structures, lower local concentration of proinflammatory cytokines), as was already documented for the other DHA metabolites, namely, docosanoids and related endocannabinoids (24)(25)(26)(27)(28)(29)(30)32). The expression of FAHFA hydrolases in WAT, liver, isolated adipocytes, and SVCs revealed that FAHFA degradation is probably regulated on both local and systemic levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results document that 13-DHAHLA has the ability to affect immune cells, alleviate macrophage activation, and stimulate the proresolving processes. It is conceivable that DHAHLA may contribute to the anti-inflammatory and proresolving effects attributed to the DHA in human and murine WAT (lower density of crown-like structures, lower local concentration of proinflammatory cytokines), as was already documented for the other DHA metabolites, namely, docosanoids and related endocannabinoids (24)(25)(26)(27)(28)(29)(30)32). The expression of FAHFA hydrolases in WAT, liver, isolated adipocytes, and SVCs revealed that FAHFA degradation is probably regulated on both local and systemic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in humans, in addition to their anti-inflammatory effects in WAT (see above), n-3 PUFAs attenuate systemic inflammatory processes (46), help to prevent cardiovascular disease (47), ameliorate nonalcoholic fatty liver disease (48), lower hypertriacylglycerolemia (49), and increase circulating adiponectin levels (50). Although n-3 PUFAs could not reverse type 2 diabetes and their impact on insulin sensitivity is controversial (23,28,34), n-3 PUFAs exert antiinflammatory effects in the WAT of human subjects with insulin resistance (28). As demonstrated by our clinical trial (34), which also served as a source of the samples for this study, n-3 PUFAs could improve postprandial lipid metabolism in overweight/obese patients with type 2 diabetes, even in the face of a combined pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study reported using NanoString nCounter system to characterize the gene expression in a patient within insulin resistant in respond to fish oil (omega-3) [38]. Other study had been reported using Illumina HiSeq 2005, Prabhakar, S.S. and colleagues to characterize the RNA expression of the kidney from diabetic rat [30].…”
Section: Next-generation Sequencingmentioning
confidence: 99%
“…Omega-3 polyunsaturated fatty acids ((0-3 PUFA) from fish oil have also antiinflammatory properties and therapeutic effects in inflammatory states including obesity (27). One of its actions is to inhibit the generation of MCP-l which has a potent chemotactic effect on both mast cells and macrophages (28) and regulate leukocyte trafficking to tissue sites of inflammation.…”
mentioning
confidence: 99%